Analisis Kepuasan Konsumen Berbelanja di Toko Tas Raja Medan - Maruli R.N; Weny Weny; Dewi Anggraini (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Tas Raja is a business engaged in bags that sells all types of bags that can be ordered online or with cash of delivery system. Established on March 8, 2016, located at Pasar Petisah Blok B No 23, West Medan. The research takes Sugiono's theory and discusses the analysis of consumer satisfaction. Tas Raja with the aim of knowing how to analyze consumer satisfaction shopping at the Tas Raja store, Medan. The writer uses the descriptive qualitative method. The source of the data used in field research (interviews) and the results of the interviews are tested by triangulation of sources. The results of this study indicate the analysis of consumer satisfaction shopping at the Tas Raja store, Medan. has been maximized and still needed to increase consumer satisfaction.